"You Just Use Your Imagination and Try to Fix It": Agential Change and International Students - Matthews, Blair (Journal of International Students, 2018)
Although interest in the experiences of international students has increased, the theoretical frameworks that are used to explain their experiences (such as culture shock, models of acculturation, cultural learning or intercultural dimensions) all share a tendency to use culture to explain behavior, denying agency, and leaving changes in the way that subjects engage with the world poorly explained. Using Margaret Archer’s concept of reflexivity (2003, 2007, 2012), this study shows how participants’ agency changes as a direct result of their experiences as international students. Drawing on case-studies of two students at a university in the southwest of England, this article shows that subjects must confront new constraints and opportunities, compelling them into reflexive deliberation, necessitating a change in agency.